THE ROLE OF MALAY CULTURE IN PROMOTING A CREATIVE ECONOMY IN THE ERA OF SOCIETY 5.0 - Selviani Selviani; Hasnah Faizah; Elmustian Elmustian; Hermandra Hermandra (Badan Penerbit STIEPARI Press, 2022)
The concept of the creative economy governs the advancement of the national economy. 7.1% of GDP is contributed by the creative economy. Malay is one of the cultures that has a considerable influence on the economy. The distinctiveness of Malay culture influences the design and function of items. A distinct culture will also influence the form of a unique product. The public has a high need for culturally-based creative industries. It is evidenced by the increase in income from the creative industry. Utilizing a qualitative strategy with descriptive analysis, the research method is qualitative. This study aims to determine Malay culture role in promoting a creative economy on 5.0 society era. This study concludes that the existence of Malay art and culture is not just dependent on convention factors related to tradition or custom (socio-cultural), but also on artistic factors that make them necessary (economic value), particularly as a tourism industry. This meaning entails the existence of processing (transformation) geared toward taking on the role of a subject of change. On the basis of the explanation provided by the tourists, it can be inferred that culturally-based creative economic items attract customers, hence promoting the creative economy. It indicates that culture plays an important role in promoting the purchase and sale of items from the creative economy.